Forgiven, not Forgotten: Communicative Translation Activities in Second Language Teaching - Prieto Arranz, J. Igor (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 2004)
Although frequently discarded and despised in the 20th century, translation now seems to find wider acceptance within the Second Language Teaching (SLT) field. However, it still has a long way to go before recovering its due place in the L2 classroom. The aim of this paper is to suggest a number of translation (and interpreting)-based activities covering the different competence levels, thus showing that communicative content and translation can perfectly go hand in hand so that old, unjustified prejudices can be superseded once and for all.